2024 IFPRI annual report - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
IFPRI’s 2024 annual report reviews highlights from our research to reduce hunger and malnutrition, including work in conflict-affected settings and on nutrition and diets, and our engagement around the world through our country and regional offices and global events.